Enhanced sulfamethoxazole degradation through ammonia oxidizing bacteria co-metabolism and fate of transformation products. (1st May 2016) - Kassotaki, Elissavet; Buttiglieri, Gianluigi; Ferrando-Climent, Laura; Rodriguez-Roda, Ignasi; Pijuan, Maite
Abstract: The occurrence of the widely-used antibiotic sulfamethoxazole (SFX) in wastewaters and surface waters has been reported in a large number of studies. However, the results obtained up-to-date have pointed out disparities in its removal. This manuscript explores the enhanced biodegradation potential of an enriched culture of Ammonia Oxidizing Bacteria (AOB) towards SFX. Several sets of batch tests were conducted to establish a link between SFX degradation and specific ammonia oxidation rate. The occurrence, degradation and generation of SFX and some of its transformation products (4-Nitro SFX, Desamino-SFX and N 4 -Acetyl-SFX) was also monitored. A clear link between the degradation of SFX and the nitrification rate was found, resulting in an increased SFX removal at higher specific ammonia oxidation rates. Moreover, experiments conducted under the presence of allylthiourea (ATU) did not present any removal of SFX, suggesting a connection between the AMO enzyme and SFX degradation. Long term experiments (up to 10 weeks) were also conducted adding two different concentrations (10 and 100 μg/L) of SFX in the influent of a partial nitrification sequencing batch reactor, resulting in up to 98% removal. Finally, the formation of transformation products during SFX degradation represented up to 32%, being 4-Nitro-SFX the most abundant. Graphical abstract: Highlights: Higher SAOR resulted in higher SFX removal in AOB biomass without adaptation. SFX was degraded up to 86% and 98% during short and long term tests, respectively. Inhibition of nitrification via ATU addition, led to null SFX removal. TPs formation represented up to 32%, the main one being 4-Nitro-SFX. An efficient UPLC-QqLIT method for TPs determination was optimized and validated.